(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The performance of hockey players is influenced by a complex interplay of physical skills and psychological factors. This study delves into the critical psychological elements that significantly impact the playing ability of competitive hockey players. By examining key aspects such as mental toughness, motivation, concentration, and emotional intelligence, this research aims to elucidate how these psychological traits contribute to on-field performance. The study draws on existing literature and empirical data to explore how mental resilience under pressure, focus during critical moments, and the ability to manage stress and anxiety can either enhance or hinder a player’s ability to perform at their peak. Additionally, the role of personality traits, such as aggressiveness and openness to experience, as well as the importance of team dynamics and social support, are analyzed to understand their influence on individual and team performance. The findings underscore the necessity for a holistic approach to training that incorporates psychological development alongside physical conditioning. By highlighting the pivotal role of psychological factors, this study offers valuable insights for coaches, sports psychologists, and players aiming to optimize performance in the highly competitive world of hockey